2018
DOI: 10.1007/s00384-018-3057-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes and benefits of ERAS program in elderly patients undergoing colorectal surgery: a case-matched study compared to conventional care

Abstract: In our experience, ERAS should be implemented without reservations in elderly patients expecting the same goals and benefits as with other age groups. Barriers in achieving a high compliance rate are common and will require a great effort in patient's education, an intensive perioperative care, and sometimes a change in the surgeons' practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 27 publications
6
21
0
Order By: Relevance
“…Similar to previous studies [18][19][20], our results showed that the implementation of ERAS program was associated with lower complications. We believe that there are several factors in the study contributing to the decrease in complications.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [18][19][20], our results showed that the implementation of ERAS program was associated with lower complications. We believe that there are several factors in the study contributing to the decrease in complications.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have shown that ERAS reduced complications and duration of hospitalization when applied to the elderly, and there was no significant difference in outcomes between the elderly and the young. [14][15][16] While the present findings are comparable to those in the literature, it may be subject to Type 2 sampling error given the sample size and the low probabilities of major adverse events, with only one patient in each cohort (age above or below 75 years) suffering from in-hospital death.…”
Section: Discussionsupporting
confidence: 71%
“…19 Advances in surgical skills and facilities, better anesthesia, fewer emergency procedures, improved access to healthcare services, and greater availability of effective treatments and postoperative care could contribute to this declining trend. [20][21][22] Furthermore, we found that the largest significant decline in 6-month mortality was in patients with lower comorbidity score, those treated at comprehensive community cancer programs, those who received surgical resection/total surgery, and those aged 75 to 79 years. Advances in perioperative management may allow patients in this group to receive the standard of care and expect similar outcomes to patients enrolled in large randomized clinical trials.…”
Section: Discussionmentioning
confidence: 72%